PENGARUH KOMUNIKASI PEMASARAN TERPADU TERHADAP KEPUTUSAN PEMBELIAN PENGUNJUNG SERTA DAMPAKNYA PADA KEPUTUSAN PERPANJANGAN SEWA PENYEWA KIOS DI PALEMBANG SQUARE MALL (PS MALL) - Hanafi, Agustina; Wahab, Zakaria (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2016)
The aim of this research is to determine the influence of integrated marketing communication to visitorÃ¢â‚¬â„¢s purchasing decisions and their impact on tenantÃ¢â‚¬â„¢s decisions for renewing contract in Palembang Square Mall. The research was conducted by distributing questionnaires to 135 visitors of PS Mall and 101 tenant leases at PS Mall. This research is using Structural Equation Modeling (SEM) with AMOS program to analyze the data. The results indicate that integrated marketing communication of PS Ã‚Â Mall significantly influence the purchasing decision of visitors but has no significant effect on tenant's decision for renewing contract. The results also indicate that visitor's purchase decision also has no significant influence to tenantÃ¢â‚¬â„¢s decision for renewing contract in Palembang Square Mall.